The effect of caffeine ingestion on skill maintenance and fatigue in epee fencers - Bottoms, L.; Greenhalgh, A.; Gregory, K. (Journal of Sports Sciences, 2013)
The ergogenic effect of caffeine on sports performance focuses predominantly on endurance sports (Doherty & Smith, 2004) with little research on intermittent high intensity sports. This study aimed to explore the effect of caffeine ingestion on skill maintenance following fencing simulated exercise. Eleven competitive fencers participated (four female; seven male; age 33 ± 6.5 years). Following a maximal test to exhaustion, fencers completed two trials assessing accuracy and reaction times (Stroop test) before and after a fatiguing protocol designed to simulate the demands of a fencing competition. Skill testing involved 30 lunges to hit a target. 500 ml placebo or 3 mg/kg caffeine supplemented drink was administered after the initial reaction and skill tests in a single-blind crossover design. The fatiguing protocol involved simulating six fights with 6-minute rests between each. Fencers rated their perceived exertion (arm, legs, overall) using the Borg scale. There was no overall effect of caffeine on total skill score (P = 0.40), however there was a tendency for fewer misses with caffeine (P = 0.10). Caffeine had no effect on the Stroop Test. Caffeine produced significantly lower perceived fatigue for overall (P < 0.01). These results provide some support for caffeine producing maintenance of skill and reducing perceived fatigue during fencing.